Pengaruh Penggunaan Model Pembelajaran Word Square Terhadap Hasil Belajar IPS Terpadu Kelas VIII SMP Negeri 1 Suralaga - Zakaki (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2024)
Quality education will create a Source of Power for a reliable and capable human being and Empower competition in the era of globalization. However in fact quality education in Indonesia is very worrying. The causes of low-quality education in Indonesia lie in yet evenly education to all citizens, efficient education, and the educational process. Study this aim for know use of learning models Word Square can influence integrated social sciences learning outcomes class VIII SMP Negeri 1 Suralaga. Types of research This is an experiment with Quasi-Experimental approaches and types of design Group Control pre-test post-est Pair. Study this located at SMP Negeri 1 Suralaga Where the population is all student class VIII at SMP Negeri 1 Suralaga school totaling 237 students and samples that is A total of 78 were taken in a way lottery that is class VIII as class control as many as 39 students and class VIII b as class Experiment as many as 39 students. Based on the results of the pre-test and post-test carried out There are enhancement results Study after treatment using the visible word square model from an average score of participants educate class pre-test experiment 51.514 and post-test 76.54 with completeness studied 26 students on the KKM value is 71, the remaining 13 are below KKM value meanwhile an average score of participants educate For group pre-test control 41.92 and post-test 74.74 with completeness study 20 students on the KKM value is 71, the remaining 19 are below KKM value. Furthermore, after testing a hypothesis, with the t-test formula, results obtained that is t count is 3.781 and the t table with db 76 at level significance 5% ie t table 1.66522, so the t count is 3,781 big from t table 1.66522, meaning the proposed Ha hypothesis accepted, that is the use of learning models word square influential in a way significant to results study Integrated Social Sciences class VIII SMP Negeri 1 Suralaga.